Subpial Schwannoma of the Cervical Spinal Cord: A Case Report and Its Intraoperative Finding Supporting a Theory of the Pathogenesis of an Intramedullary Schwannoma - Decharin, Payothorn; Suvithayasiri, Siravich; Nivatpumin, Padungcharn; Trathitephun, Warayos (Asian Journal of Neurosurgery, 2022)
Because of its tumor origin from nerve sheath cells (the Schwann cells), the pathogenesis of an extraordinary rare intramedullary schwannoma, which should not have any Schwann's cells in nature, is controversial and still in debate. We report a case of a 63-year-old man diagnosed with a cervical cord intramedullary schwannoma with an interesting intraoperative finding that could support one of the theories on its genesis.
Keywords: subpial schwannoma; intramedullary schwannoma; pathogenesis; cervical cord tumor